Clan Politics in Village Head Elections: a Case Study of the 2021 Haunatas I Village Head Election and the 2023 Siraja Gorat Village Head Election, Toba Regency, North Sumatra Province - Lubis, Timoteus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
in the village head elections of Haunatas I and Siraja Gorat. Many studies on this topic show that clans often prioritize resources or power. The distribution of resources and power serves as a bargaining chip for clan elites in determining their stance. On the other hand, if an agreement is reached between clans, the possibility of open competition between clans can be minimized. However, if disagreements arise between clans, competition will ensue, potentially triggering inter-clan conflict. The theory applied in this study is the clan politics theory proposed by Kathleen Collins, using qualitative research methods through a case study approach in the 2021 Haunatas I village head election and the 2023 Siraja Gorat village head election. The results show that both villages implemented a village head election mechanism based on inter-clan agreement. However, only Haunatas I village successfully maintained and achieved this agreement. This study found that informal negotiation processes and mediation efforts significantly influenced the continuity and achievement of inter-clan agreements.